The reality of School Ergonomics: A study on a sample of primary schools in the wilaya of Constantine - Benabderrahmane, Tahar; Chinoune, Sid ameur (Journal of Human Sciences, 2022)
The aim of this study is to uncover the reality of school ergonomics from the point of view of a sample of primary school teachers in the Wilaya of Constantine. In order to achieve the objectives of the study, the researchers adopted the descriptive method. The researchers constructed a tool to measure the attitudes of the teachers towards the reality of school ergonomics. The tool consisted of (24) items belonging to four axes, which were applied to a sample of (47) teachers in some Constantine schools. The study found that school ergonomics is up to the required level from the point of view of the teachers through the dimensions: school buildings, classrooms, educational means, Physical Conditions.